Old-age provisions in Germany: Changes in the retirement system since the 1980s - Markus Wörz (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2011)
Pensions absorb the largest share of the welfare state in financial terms. This is true not only in the aggregate but also for individuals. Financial security in old age is of key importance. The provision of financial security, however, is contingent upon the institutional arrangement of social security systems. This paper describes key features of Statutory Pension Insurance (SPI), the most important provision for financial security in old age from which most senior citizens derive the largest part of their retirement income. It focuses next on core SPI features: How benefits are calculated; important changes since the 1980s; and, how these changes affect average pensions. With various routes into retirement - particularly in Germany - the following chapter then discusses these different paths and how they were reformed over time. Following that, occupational and private pensions are examined as alternative means to oldage financial security other than SPI. Here we do so with empirical data showing the evolution of different, old-age income sources since the 1990s. This institutional description shows that SPI became less generous between 1980 and 2007: First, the pension formula has been modified several times resulting in shrinking benefits. The introduction of actuarial reductions, in 1997, for early enrolment of benefits amplified this, since a considerable number of people retire before the statutory retirement age and, therefore, receive lower pensions. Moreover, in several steps, university education has been completely disregarded in the valuation of pensions. At the same time, credits were given for child-raising and child-care services. Whereas the former is already in force, the latter will only benefit future generations of pensioners. Thus, those most affected by welfare state changes in relation to old-age pensions are pensioners who retire early and have higher education.
Keywords: 300; Gesetzliche Rentenversicherung; Rentenreform; Einkommen; Rentner; Deutschland